Ancient river systems and phylogeographical structure in the spring salamander, Gyrinophilus porphyriticus - Shawn R. Kuchta; Michael Haughey; Addison H. Wynn; Jeremy F. Jacobs; Richard Highton (Journal of Biogeography, 2016)
Aim The river drainages of the Appalachian Mountains have experienced a dynamic history as glacial cycles, stream capture and other geological processes have led to the fragmentation and fusion of formerly isolated palaeodrainages. Some ancient rivers have gone extinct, including portions of the great Teays River. Here we investigate the contribution of contemporary and historical drainages to patterns of phylogeographical structure in the spring salamander complex, Gyrinophilus porphyriticus . Location Eastern North America, USA . Methods Sampling spanned the range of the G. porphyriticus complex, and included representative samples of the cave species of Gyrinophilus as well. Molecular sequence data included the mitochondrial DNA locus cytochrome b and the nuclear locus recombination‐activating gene 1 ( RAG ‐1). Time‐calibrated phylogenies were inferred, and Bayes‐ LAGRANGE was used to reconstruct ancestral distributions. Contemporary and historical river influences on patterns of genetic diversity were tested using distance‐based redundancy analysis (db‐ RDA ). Results The G. porphyriticus complex originated prior to the Pleistocene glacial cycles, and historical river systems explained more genetic variation than did contemporary drainages or geographical distance. Patterns of genetic variation suggest that extinct or remodelled palaeodrainages, including the Teays River, played an important role in structuring contemporary patterns of genetic variation. Main conclusions The hydrogeological history of eastern North American drainage basins has been instrumental in structuring patterns of regional biodiversity in freshwater species. Here we show that hydrological remodelling has also left its genetic signature in the semi‐aquatic spring salamander complex, G. porphyriticus . Historical drainages accounted for the largest fraction of phylogeographical structure, more so than did contemporary drainages or geographical distance, with spatial and temporal patterns of variation associated with the extinct Teays River.